The interactive medical simulation toolkit (iMSTK): an open source platform for surgical simulation - Moore, Jacob; Scheirich, Harald; Jadhav, Shreeraj; Enquobahrie, Andinet; Paniagua, Beatriz; Wilson, Andrew; Bray, Aaron; Sankaranarayanan, Ganesh; Clipp, Rachel B. (Frontiers in Virtual Reality, 2023)
Human error is one of the leading causes of medical error. It is estimated that human error leads to between 250,000 and 440,000 deaths each year. Medical simulation has been shown to improve the skills and confidence of clinicians and reduce medical errors. Surgical simulation is critical for training surgeons in complicated procedures and can be particularly effective in skill retention. The interactive Medical Simulation Toolkit (iMSTK) is an open-source platform with position-based dynamics, continuous collision detection, smooth particle hydrodynamics, integrated haptics, and compatibility with Unity and Unreal, among others. iMSTK provides a wide range of real-time simulation capabilities with a flexible open-source license (Apache 2.0) that encourages adoption across the research and commercial simulation communities. iMSTK uses extended position-based dynamics and an established collision and constraint implementations to model biological tissues and their interactions with medical tools and other tissues. The platform demonstrates performance that is compatible with real-time simulation that incorporates both visualization and haptics. iMSTK has been used in a variety of virtual simulations, including for laparoscopic hiatal hernia surgery, laparoscopic cholecystectomy, osteotomy procedures, and kidney biopsy procedures.